Development of a core set of gait features and their potential underlying impairments to assist gait data interpretation in children with cerebral palsy - van der Krogt, Marjolein M.; Houdijk, Han; Wishaupt, Koen; van Hutten, Kim; Dekker, Sarah; Buizer, Annemieke I. (Frontiers in Human Neuroscience, 2022)
Background: The interpretation of clinical gait data in children with cerebral palsy (CP) is time-consuming, requires extensive expertise and often lacks transparency. Here we aimed to develop a set of look-up tables to support this process, linking typical gait features as present in CP to their potential underlying impairments. Methods: We composed a set of gait features and their potential underlying impairments based on biomechanical reasoning, literature and clinical experience. This set was further specified through a Delphi process in a multidisciplinary group of experts in gait analysis of children with CP and evaluated on 20 patient cases. The likelihood of the listed gait feature – impairment relationships was scored by the expert panel on a five-point scale. Results: The final set included 118 relevant gait feature – impairment relations including likelihood scores. This set was presented in the form of look-up tables in both directions, i.e. sorted by gait features with potential underlying impairment, and sorted by impairments with potential related gait features. The average likelihood score for the relations was 3.5 ± 0.9 (range 2.1 – 4.6). Conclusion: The developed set of look-up tables linking gait features and impairments, can be used to assist gait analysts and clinicians in standardized clinical reasoning and treatment decisions for gait impairments in children with CP.